Effects of intravenous morphine and lidocaine on bacterial growth - Cristiana Iulia Osoian; Stanca Lucia Pandrea; Mirela Flonta; Adrian Florea; Luminita Matros; Daniela Ionescu (BMC Anesthesiology)
Abstract Background Infection prevention and control remain critical challenges in the ICU. Morphine, a frequently used opioid for postoperative pain management, may indirectly promote infections, whereas lidocaine might have protective effects. However, data regarding the direct influence of morphine and lidocaine, at concentrations within the range of plasma concentrations, on common ICU bacterial strains are lacking. This is the first study to investigate the direct effects of morphine and lidocaine at plasma concentrations corresponding to possible clinical settings, as seen in multimodal analgesia regimens, on bacterial growth using microbiological assays and transmission electron microscopy. Methods Morphine (1000 ng/ml, 2000 ng/ml) and lidocaine (4 µg/ml, 10 µg/ml) were placed in contact with standard strains of Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus and tested using diffusion method, broth dilution method, and time-kill assay. Additionally, E. coli, P. aeruginosa and S. aureus were exposed to lidocaine 10 µg/ml and examined via transmission electron microscopy. Results Morphine and lidocaine exhibited neither stimulatory nor inhibitory effects on bacterial growth, regardless of concentration, volume, or exposure time in microbiological testing. In contrast, transmission electron microscopy revealed that lidocaine exposure altered bacterial ultrastructure, causing significant cell wall disorganization and rupture, alterations in cytoplasmic and nucleolar structure, and the appearance of “ghost cells”, indicative of cell lysis. Conclusions At plasma concentrations, morphine and lidocaine do not directly affect bacterial growth in vitro microbiological laboratory testing. Lidocaine on the other hand, in higher plasma concentrations, disrupts bacterial ultrastructure. Further studies are needed to investigate the significance and clinical impact of these findings.